Teacher Learning that Matters: international perspectives - Kooy,Mary and Veen,Klaas.Van; Kooy,Mary and Veen,Klaas.Van (New York Routledge Taylor & Francis Group, 2012)
This book weaves together major studies, research findings and theoretical orientations to represent a globalized network of inquiries into the what, how and why of teacher learning that shapes teacher skill and knowledge. Teacher learning matters on an international scale because teachers are the portals through which any initiative for change and reform is realized. Recognizing that a highly skilled teaching force is instrumental to improving student achievement adds import to generating interactive dialogue on teacher learning around the globe.
Includes index
Keywords: Education / Aims & Objectives, Education / General, Education / Philosophy, Theory & Social Aspects, Education / Professional Development, Education / Research, Education / Teacher Training & Certification, Education / Teaching / General, Electronic books, Professional learning communities -- Cross-cultural studies, School improvement programs -- Cross-cultural studies, Teachers -- Cross-cultural studies -- In-service training -- Professional relationships, College teachers -- Cross-cultural studies -- Professional relationships, Teachers -- Cross-cultural studies -- In-service training